Supporting coaching actions for the Finnish XC skiing national team - Hynynen, E.; Mikkola, J.; Vesterinen, V. (Post Olympic Winter Games 2018, Vuokatti, 28.-29.6.2018, 2018)
Support during training camps Test camps Support between the camps Videos of tests, simulation of track profiles etc